-15-(-18)=

Simple and best practice solution for -15-(-18)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15-(-18)= equation:


-15-(-18)=0

We simplify the equation to the form, which is simple to understand
-15-(-18)=0

Remove unnecessary parentheses
-15+18=0

We move all terms containing to the left and all other terms to the right.
0=0+15-18

We simplify left and right side of the equation.
0=-3

0=-3

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 710=310+0.04t | | 4x^2-14x+49=0 | | 18g-13g+1=11 | | 2x-5(x-3)=-9+4x+3 | | 4(r-12)=16 | | 3x+3=3(x+4)-4 | | 5b+4b=-17 | | 6x+2=-7+2x+17 | | q-17/1=-2 | | 7x-17t+2x=2-8x+15 | | -x+10=12 | | -11s+2s=9 | | 6*x=12 | | k^2-10k+24= | | 2(3n+2)=7(4n+9)+4 | | 11x-9=4x+68 | | -12c+16c=-12 | | 80=5(5n-4) | | v+7/2=3 | | 3y+5y=13 | | 4x+7=3+2x+22 | | -3m^2+16=-284 | | 10k-6=-156 | | -2(x+2)-3(x+6)=-22 | | 4x^2+81=17 | | 3x=15x^2 | | (5x^2)-(6x)-(2)=0 | | x(-4)=8 | | -7(-3x+3)=-105 | | (-5)*x=1/2 | | -2(n-3)=-4 | | 9(x+7)=81 |

Equations solver categories